INDICES NEOTECTONIQUES DANS LES SEDIMENTS DU LAC IFRAH (MOYEN ATLAS, MAROC) - Sadkaoui, Driss; Benabdelhadi, Mohammed; Deffontaines, Benoît; Chaouni, Abdel-Ali; Ntarmouchant, Ahmed; Baali, Abdennasser; Benzouggagh, Brahim; Gourari, Lahcen (European Scientific Journal, ESJ, 2015)
In the north-eastern edge of the Tizi n’Trehtene Fault zone, situated within the Causse Atlasic, several lakes are aligned in the NE-SW direction. Among these lake Dayet Ifrah occupies the northern part of a polje of Amekla. This lake is fed by a small river (ravine) flowing from the south-west of its catchment area. This ravine erode the lake sediments and changes abruptly direction several times to accommodate with two discoveries faults and studied here. The lacustrine sediments sequence on which are seen on both river bank shows faults with vertical offsets, fills of the grabens, and seismic structures related to quaternary re-activation of the Tizi n’Terhtene Fault zone. If we correlate the dated sediments of the carrots issued in the Ifrah lake and the lacustrine sediments situated around the river, they ought to have 8420 ±50 years 14C B.P. and the neotectonic structures correspond to an Holocene distensif or transtensif neotectonic episode.